Venous drainage of lumbar vertebral bodies: anatomic study with application to kyphoplasty, vertebroplasty, and pedicle screw complications - Iwanaga, Joe; Rustagi, Tarush; Ishak, Basem; Johal, Jaspreet; David, Glen; Reina, Miguel Angel; Dumont, Aaron S.; Tubbs, R. Shane (World neurosurgery, 2020)
Background - Bone cement augmentation with polymethylmethacrylate is a reliable method for stabilizing osteoporotic compression fractures and improving fixation of pedicle screws. However, cement extrusion into the vertebral venous system can result in pulmonary cement embolism. The goal of this anatomic study was to identify the relationship between the internal/external vertebral plexus and neighboring abdominal caval system. - Methods - Thirty-two lumbar vertebral levels were used in this study. Anterior abdominal dissection was performed to access the lumbar vertebral bodies through the peritoneal cavity, and a 16-gauge needle was placed into the center of each lumbar vertebral body at its anterior aspect. Fluoroscopy was used to confirm if the needle was correctly placed. Next, latex and/or continuous air injections were performed into each lumbar vertebral level (L1-L5). Observations confirmed if the latex or air traveled into the inferior vena cava. In addition, the spinal canal was opened to see if any latex was found to enter inside the vertebral canal in cadavers injected with the latex. - Results - Latex or air was found to flow into the inferior vena cava at all the lumbar vertebral levels. The latex/air was not observed in the spinal canal in any specimen. - Conclusions - An exact knowledge of the lumbar vertebral venous anatomy is essential when procedures that could affect the vertebral venous system are involved. Its complexity and anatomic variability necessitate such an understanding to better prevent/understand possible complications associated with polymethylmethacrylate extrusion.